Oxaliplatin‐induced enteric neuronal loss and intestinal dysfunction is prevented by co‐treatment with BGP‐15. (11th January 2018) - McQuade, Rachel M; Stojanovska, Vanesa; Stavely, Rhian; Timpani, Cara; Petersen, Aaron C; Abalo, Raquel; Bornstein, Joel C; Rybalka, Emma; Nurgali, Kulmira
Abstract : Background and Purpose: Gastrointestinal side effects of chemotherapy are an under‐recognized clinical problem, leading to dose reduction, delays and cessation of treatment, presenting a constant challenge for efficient and tolerated anti‐cancer treatment. We have found that oxaliplatin treatment results in intestinal dysfunction, oxidative stress and loss of enteric neurons. BGP‐15 is a novel cytoprotective compound with potential HSP72 co‐inducing and PARP inhibiting properties. In this study, we investigated the potential of BGP‐15 to alleviate oxaliplatin‐induced enteric neuropathy and intestinal dysfunction. Experimental Approach: Balb/c mice received oxaliplatin (3 mg·kg −1 ·day −1 ) with and without BGP‐15 (15 mg·kg −1 ·day −1 : i.p.) tri‐weekly for 14 days. Gastrointestinal transit was analysed via in vivo X‐ray imaging, before and after treatment. Colons were collected to assess ex vivo motility, neuronal mitochondrial superoxide and cytochrome c levels and for immunohistochemical analysis of myenteric neurons. Key Results: Oxaliplatin‐induced neuronal loss increased the proportion of neuronal NO synthase‐immunoreactive neurons and increased levels of mitochondrial superoxide and cytochrome c in the myenteric plexus. These changes were correlated with an increase in PARP‐2 immunoreactivity in the colonic mucosa and were attenuated by BGP‐15 co‐treatment. Significant delays in gastrointestinal transit, intestinal emptying and pellet formation, impaired colonic motor activity, reduced faecal water content and lack of weight gain associated with oxaliplatin treatment were restored to sham levels in mice co‐treated with BGP‐15. Conclusion and Implications: Our results showed that BGP‐15 ameliorated oxidative stress, increased enteric neuronal survival and alleviated oxaliplatin‐induced intestinal dysfunction, suggesting that BGP‐15 may relieve the gastrointestinal side effects of chemotherapy.